Modification of the flowering dynamics of pineapple (Ananas comosus L.) cv. ‘MD2’ using Aviglycine in the central jungle of Perú - Bello-Amez, Segundo (2022)
Pineapple (Ananas comosus) is a widely cultivated fruit in tropical countries. However, its natural flowering (NF) is a physiological event that can make harvesting difficult, bringing with it financial problems. Therefore, this study aimed to determine the effect of Aviglycine (AVG) on the flowering of pineapple cv. ‘MD2’ in the central jungle of Peru. Three doses (150 mg/L, 250 mg/L, and 350 mg/L) of AVG (commercial product ReTain 15%) were studied with six and eleven applications. The results confirmed the appearance of NF under Satipo conditions. The high doses of AVG (250 mg/L and 350 mg/L) inhibited the appearance of inflorescences in almost all evaluations and particularly with eleven applications compared with the treatment without AVG and flower induction (NF). The NF presented three periods with different relative rates of inflorescence appearance (RRIA), where the first period had the highest RRIA and longest duration (42 d). In conclusion, the application of AVG had a significant effect in delaying the appearance of inflorescences; thus, its application in pineapple cultivation is recommended. However, more studies are needed to further deepen the knowledge on the management of this growth regulator.